2011
DOI: 10.1186/1476-4598-10-69
|View full text |Cite
|
Sign up to set email alerts
|

A chalcone-related small molecule that induces methuosis, a novel form of non-apoptotic cell death, in glioblastoma cells

Abstract: BackgroundMethuosis is a unique form of non-apoptotic cell death triggered by alterations in the trafficking of clathrin-independent endosomes, ultimately leading to extreme vacuolization and rupture of the cell.ResultsHere we describe a novel chalcone-like molecule, 3-(2-methyl-1H- indol-3-yl)-1-(4-pyridinyl)-2-propen-1-one (MIPP) that induces cell death with the hallmarks of methuosis. MIPP causes rapid accumulation of vacuoles derived from macropinosomes, based on time-lapse microscopy and labeling with ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
192
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(207 citation statements)
references
References 69 publications
13
192
2
Order By: Relevance
“…Its physiological role might be in homeostatic responses to nutrient deprivation. A recent study has shown that TORC1 inhibits the utilisation of extracellular protein that has been ingested through macropinocytosis, suggesting that this growthregulatory complex is intimately connected with the control of macropinocytosis in the context of nutrient acquisition (Palm et al, 2015). Further investigations into the normal developmental and homeostatic roles of CendR-mediated macropinocytosis in vertebrate cells, and its effects on vascular permeability (Pang et al, 2015), could thus not only lead to its use as a therapeutic tool but could also help to improve our understanding of its evolutionary relationships with other uptake mechanisms.…”
Section: Using Macropinocytosis As a Route For Delivery Of Macromolecmentioning
confidence: 99%
See 2 more Smart Citations
“…Its physiological role might be in homeostatic responses to nutrient deprivation. A recent study has shown that TORC1 inhibits the utilisation of extracellular protein that has been ingested through macropinocytosis, suggesting that this growthregulatory complex is intimately connected with the control of macropinocytosis in the context of nutrient acquisition (Palm et al, 2015). Further investigations into the normal developmental and homeostatic roles of CendR-mediated macropinocytosis in vertebrate cells, and its effects on vascular permeability (Pang et al, 2015), could thus not only lead to its use as a therapeutic tool but could also help to improve our understanding of its evolutionary relationships with other uptake mechanisms.…”
Section: Using Macropinocytosis As a Route For Delivery Of Macromolecmentioning
confidence: 99%
“…Screens have identified small molecules that can induce this form of death in malignant cells, offering hope for new treatments of glioblastoma (Overmeyer et al, 2011;Kitambi et al, 2014). The precise cause of cell death is not clear in some instances of methuosis (Maltese and Overmeyer, 2014), but in acute druginduced vacuolisation, the cytoplasmic swelling causes the plasma membrane to rupture (Overmeyer et al, 2011;Kitambi et al, 2014).…”
Section: Macropinocytosis In Life and Death -Roles For Rasmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to our observations in MEDs, hyperstimulation of macropinocytosis has also been found to result in cell death in some human GB cell lines as well as in other cancer cell lines (19)(20)(21)(22). Interestingly, overexpression of oncogenic Harvey-Ras Cell culture and transfections.…”
mentioning
confidence: 97%
“…[65] In 2011 the same group reported an indole named MIPP (Figure 14(a)) which induced methuosis in a glioblastoma cell line. [66] In 2012 they reported on a small library of MIPP analogues, and attempted to elucidate structure-activity relationships when tested against the glioblastoma cell line U251. [67] group, implying that this structural change is responsible for the improvment in activity.…”
Section: Methuosis Initiatorsmentioning
confidence: 99%